Transformasi Relasi Sosial Akibat Kecerdasan Buatan dalam Praktik Kerja Kreatif Humaniora Digital - Hakim, Hamdan; Aziz, Teuku Ilham (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The development of artificial intelligence has brought significant changes to digital humanities practices, particularly in creative work that involves the production and interpretation of cultural knowledge. This study aims to analyze the transformation of social relations resulting from the integration of artificial intelligence into creative work practices in digital humanities. The main focus is on changes in interaction patterns, collaboration structures, role distribution, the formation of professional identities, and ethical dynamics that emerge in relations between humans and AI systems. The study adopts an interpretative qualitative approach with a multiple case study design. Data were collected through in-depth interviews, limited participant observation, and analysis of digital artifacts produced in AI-based creative practices. Data analysis was conducted thematically to identify patterns of social relations and meanings constructed by creative workers. The findings show that artificial intelligence is no longer positioned solely as a technical tool, but as a relational entity that plays an active role in the creative process. The presence of AI shifts interaction patterns toward hybrid human–machine relations, reconfigures work collaboration, and influences the legitimacy and identity of creative workers. This transformation is ambivalent. It opens opportunities for creative exploration while also generating tensions related to authority, the value of creativity, and inequalities in access to technology. This study emphasizes the importance of a critical digital humanities approach that is oriented toward human values in responding to the integration of artificial intelligence. The findings are expected to provide empirical and conceptual contributions to the development of digital humanities studies in the era of artificial intelligence.